2020
DOI: 10.1002/fee.2189
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐change refugia: biodiversity in the slow lane

Abstract: Climate‐change adaptation focuses on conducting and translating research to minimize the dire impacts of anthropogenic climate change, including threats to biodiversity and human welfare. One adaptation strategy is to focus conservation on climate‐change refugia (that is, areas relatively buffered from contemporary climate change over time that enable persistence of valued physical, ecological, and sociocultural resources). In this Special Issue, recent methodological and conceptual advances in refugia science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
208
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 184 publications
(211 citation statements)
references
References 49 publications
2
208
0
1
Order By: Relevance
“…As noted above, we assumed that the amount of change will be the same for all locations across the landscape, and that locations will differ only in their initial topoclimate conditions. At present, however, we lack sufficient data to project whether some sites will be buffered and experience less change than others, information that is critical to the broader discussion of potential refugia (Morelli et al 2020).…”
Section: Species Distribution Models and Future Projectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted above, we assumed that the amount of change will be the same for all locations across the landscape, and that locations will differ only in their initial topoclimate conditions. At present, however, we lack sufficient data to project whether some sites will be buffered and experience less change than others, information that is critical to the broader discussion of potential refugia (Morelli et al 2020).…”
Section: Species Distribution Models and Future Projectionsmentioning
confidence: 99%
“…Because they contain a wide range of microclimatic conditions, heterogeneous landscapes are also expected to harbor climate refugia (Ashcroft 2010;Hannah et al 2014;Morelli et al 2017). Although defining climate refugia remains a subject of debate (Keppel et al 2012;Morelli et al 2020), we focus on the landscape scale, and on whether species occupying cool and/or moist locations will be more vulnerable to a warming climate than species in warm and/or dry locations. Cool microsites are often viewed as potential refugia (eg Gollan et al 2014), given that they harbor species adapted to cooler climates, but this notion has also been called into question because these particular species may be the most vulnerable to further warming.…”
mentioning
confidence: 99%
“…Amid these concerns is a growing recognition of the importance of refugia, and especially disturbance refugia, as critical buffers to rapid ecosystem change (Morelli et al . ).…”
mentioning
confidence: 97%
“…Thus, active conservation and climate-adaptation strategies are needed to prevent biodiversity loss (Millar et al 2007). The identification, conservation, and restoration of potential climate-change refugia (Morelli et al 2016(Morelli et al , 2020 can provide protection for biodiversity without the risks associated with other approaches (e.g., translocation, Schwartz et al 2012). Step 1: Identify the species and relevant habitats to be prioritized for conservation.…”
Section: Looking To the Futurementioning
confidence: 99%
“…However, identifying habitats that will retain cold conditions and serve as climate refugia can be difficult ( Figure 5; Morelli et al 2016Morelli et al , 2020. While advances have been made in predicting topographic and landscape features that support cool micro-climates (Dobrowski et al 2011), CRLs can be readily identified via satellite imagery and aerial photography due to their distinct geomorphology (e.g., Cremonese et al 2011).…”
Section: Looking To the Futurementioning
confidence: 99%